Contested places, contested pasts: Sites of memory and commermoration in the hungarian landscape - Foote, Kenneth E.; Arvay, Anett (London Routledge, 2025)
This is the first comprehensive, book-length study of Hungary$1 (Bs commemorative landscapes from the First World War to the present. By stressing the spatiality and materiality of memory practice, it offers new insights into why some events are celebrated widely, while other controversial events are marked modestly or not at all. s